Stabilization of highly efficient perovskite solar cells with a tailored supramolecular interface - Chenxu Zhao; Zhiwen Zhou; Masaud Almalki; Michael A. Hope; Jiashang Zhao; Thibaut Gallet; Anurag Krishna; Aditya Mishra; Felix T. Eickemeyer; Jia Xu; Yingguo Yang; Shaik M. Zakeeruddin; et al. (Nature Communications, 2024)
Abstract The presence of defects at the interface between the perovskite film and the carrier transport layer poses significant challenges to the performance and stability of perovskite solar cells (PSCs). Addressing this issue, we introduce a dual host-guest (DHG) complexation strategy to modulate both the bulk and interfacial properties of FAPbI3-rich PSCs. Through NMR spectroscopy, a synergistic effect of the dual treatment is observed. Additionally, electro-optical characterizations demonstrate that the DHG strategy not only passivates defects but also enhances carrier extraction and transport. Remarkably, employing the DHG strategy yields PSCs with power conversion efficiencies (PCE) of 25.89% (certified at 25.53%). Furthermore, these DHG-modified PSCs exhibit enhanced operational stability, retaining over 96.6% of their initial PCE of 25.55% after 1050 hours of continuous operation under one-sun illumination, which was the highest initial value in the recently reported articles. This work establishes a promising pathway for stabilizing high-efficiency perovskite photovoltaics through supramolecular engineering, marking a significant advancement in the field.